Introduction to CMOS OP-AMPs and comparators - Gregorian, Roubik (Wiley, 1999)
A step-by-step guide to the design and analysis of CMOS operational amplifiers and comparators This volume is a comprehensive text that offers a detailed treatment of the analysis and design principles of two of the most important components of analog metal oxide semiconductor (MOS) circuits, namely operational amplifiers (op-amps) and comparators. The book covers the physical operation of these components, their design procedures, and applications to analog MOS circuits-particularly those involving switched-capacitor circuits, and analog-to-digital (A/D) and digital-to-analog (D/A) converters. Roubik Gregorian, a leading authority in the field, gives circuit designers the technical knowledge they need to design high-performance op-amps and comparators suitable for most analog circuit applications. In this self-contained treatment, which is loosely based on his well-received 1986 book, Analog MOS Integrated Circuits for Signal Processing (coauthored with Gabor C. Temes), Gregorian reviews the required basics before advancing to state-of-the-art topics and problem-solving techniques. This valuable guide: Clearly explains configuration and performance limitation issues affecting the operation of CMOS op-amps and comparators Details advanced design procedures to improve performance Provides practical design examples suitable for a broad range of analog circuit applications Incorporates hundreds of illustrations into the text Concludes each chapter with problems and references to advanced topics, useful in textbook adoptions Introduction to CMOS Op-Amps and Comparators is invaluable for analog and mixed-signal designers, for senior and graduate students in electrical engineering, and for anyone who would like to keep up with this essential technology.